Analisis Perlakuan Akuntansi Tabungan Haji Pada Bank Mega Syariah Cabang Pekanbaru - Dariana Dariana (LPPM ISNJ Bengkalis, 2012)
This research aims to provide information about the management of savings hajj on Syariah banking and provides a description of the accounting treatments practice. Unit to be analyzed in this research is accounting treatment which includes the recognition, measurement, the presentation of, and disclosure over savings products with the principle mudharabah the on Megas Syariah banking. Data collection method are direct observation, documentation, and interview. Criteria used in this research have met recognition of mudharabah, measurement of mudharabah, and presentation of Mudharabah. Based on the analysis, it is found recognition recognized In accordance of the nominal value or the amount of money paid up capital of the company shall. The measurement of counted based on the amount of money paid up capital of the company shall and calculation the ratio in accordance with the provisions of PT. Bank Mega Syariah. Savings of the hajj served in the balance sheet and profit and loss statement. Savings of the hajj expressed into savings mudharabah.